Circular electrodes stepping manipulation platform for A549 cancer cell detection. (24th May 2019) - Loc, Do Quang; Trang, Nguyen Thu; Lan, Vo Thi Thuong; Nhung, Hoang Thi My; Ha, Tran Thi Thuy; Chieu, Le Van; Viet, Nguyen Ngoc; Jen, Chun-Ping; Tung, Bui Thanh; Duc, Trinh Chu
In this paper, a novel design of an impedance sensor integrated on stepping dielectrophoresis manipulation platform for biological cells detection is presented. The platform consists of fluidic working chamber and manipulating/sensing gold electrodes. Gold electrodes are patterned on glass substrate with an insulating layer covered to avoid the direct contact between metal electrodes and electrolyte. The outer electrodes implement biological cell manipulating function while the inner electrodes construct sensing electrodes pair which are connected to an impedance analyser to detect the appearance of biological cells on the sensing area. In this work, several experiments have been implemented to investigate the performance of A549 cell line trapping ability based on aptamer immobilisation on gold surface method with different concentrations of aptamer solution. Impedance spectroscopy responses of the proposed sensor with frequency ranges from 10 kHz to 1.0 MHz are examined. The impedance spectroscopy shows an impedance change of up to approximately 2500 Ω at 200 kHz when 16 A549 cells appear in the sensing area.